KESULITAN DALAM MENERAPKAN KURIKULUM MERDEKA DALAM SOAL CERITA MATEMATIKA DI SEKOLAH DASAR - Nurhaswinda; Afdiliani, Wilda; Pinanti; Ardelia, Vania; Indah Handayana, Dian; Fitrah, Audylla; Aulia, Fitri; Ainur Rahma, Annisa; Qonitah, Atiyah; Meizura, Amanda (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The independent learning curriculum has been implemented in the third year, have been completed using the Independent Curriculum. This Independent Curriculum is very flexible to implement. The method used in this study is a descriptive narrative method with a qualitative approach. The results of this study are that there are difficulties in implementing the Independent Curriculum felt by teachers such as teacher training and readiness which are still lacking where teacher training is one cluster and then carried out independently from YouTube, many learning models are not yet known and understood by teachers so that teachers are confused about using learning models when implementing the Independent Curriculum.